Developing Interactive Video Learning Media Using Sparkol Videoscribe on Plane Geometry for Grade III Elementary School Students - Egi Amaza Mawaddah; Yantoro Yantoro; Muhammad Sholeh (Lembaga Sosial Rumah Indonesia, 2026)
Purpose – This study aims to develop interactive video learning media using Sparkol Videoscribe on plane geometry material for grade III elementary school students. This research is motivated by the need for learning media that can support the visualization of abstract mathematical concepts at the elementary school level. Methods – This research uses a research and development (R&D) design with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects involved grade III students as well as expert validators consisting of material experts, media experts, and linguists. Data collection techniques use observation, interviews, questionnaires, and tests. The data was analyzed descriptively, quantitatively, and qualitatively to determine the level of validity and practicality of the developed media. Findings – The results of the study showed that the media developed had a high level of validity, with a percentage of 96% of material experts, 93.85% of media experts, and 90% of linguists, with an average of 93.23% being in the very valid category. From the practical aspect, the teacher's response reached 96%, the small group test was 91.67%, and the limited group test was 93.33%, with an average of 93.67%, which was in the very practical category. These results show that the developed media are suitable for use in mathematics learning on plane geometry materials on a limited scale.Research Implications – This study shows that interactive video learning media using Sparkol Videoscribe have the potential as a learning innovation that can support concept visualization, support student involvement, and can be used to assist teachers in delivering material.